New species of Sparianthina Banks, 1929 (Araneae: Sparassidae: Heteropodinae) - Rheims, Cristina Anne (Zootaxa, 2011)
Two new species of Sparianthina Banks, 1929 are described: S. parang sp. nov. based on males and females from Tobago, and S. gaita sp. nov. based on a male and a female from Venezuela. Both species present the heavy dorsal tegular apophysis on the male palps and the multilobed internal duct system in the vulvae, with very long fertilization ducts that are characteristic of the genus.